Analisis Penerapan Standar Akuntansi Keuangan Pesantren di Pondok Pesantren Amanatul Ummah Surabaya - Ghofirin, S.Pd., M.Pd, Mohammad; Dina Anggraeni Susesti (Universitas Nahdlatul Ulama Surabaya, 2024)
Islamic boarding schools are non-profit entities and have a very important role inpreparing financial reports. Until now, there are still many Islamic boarding schools that recordfinancial reports simply. This can be influenced by several factors, the lack of understanding byHR regarding the presentation of financial reports is the main factor. Bank Indonesia has initiatedIslamic Boarding School Accounting Guidelines (PAP) as a solution to the problem of preparingfinancial reports in Islamic boarding schools. This research aims to determine the form of recordingfinancial reports and to analyze the implementation of recording financial reports based onFinancial Accounting Standards (SAK) at the Amanatul Ummah Islamic boarding school inSurabaya. The method used in this research is qualitative with a descriptive approach. Datacollection techniques will be carried out by observation and interviews.